Struktur Komunitas Makrozoobentos dan Kaitannya dengan Kualitas Perairan Kampung Baru Desa Sebong Lagoi Kabupaten Bintan - Wahyu Muzammil; Nova Prihatin; Winny Retna Melani (Tropical Fisheries Management Journal, 2021)
Kampung Baru is an area on Bintan Island which is located in Sebong Lagoi Village, Teluk Sebong District, Bintan Regency, Riau Islands Province. This study aimed at determine the structure of the macrozoobenthos community, the condition of the physico-chemical parameters of the waters and the relationship between macrozoobenthos and water quality. This research was conducted using a survey method. Sampling site points of this study using random sampling method with 30 sampling site points at high and low tide. The parameters measured are physical, chemical and biological parameters of the water. The results showed that there were 18 species of macrozoobenthos consisting of 4 classes of macrozoobenthos and 3 phylum at 30 sampling site points, namely mollusca, annelida, and arthhopoda phylum. Based on the ecological index value, it is known that the macrozoobenthos species in Kampung Baru waters are still classified as low with disproportionate conditions. The values ​​of diversity index (low), uniformity index (high) and dominance index (low). Water quality of Kampung Baru waters at high tide still meet quality standards of Kepmen-LH No. 51 of 2004, but at low tide the values ​​of temperature, DO, and salinity parameters did not meet quality standards. The relationship between macrozoobenthos parameters and water quality using PCA analysis where density parameters have a relationship with two parameters, namely temperature and pH.